Pengaruh CSR, Reputasi dan Ekuitas Merek pada Kinerja Bisnis: RBV Perspektif (CSR’s Impact, Reputation and Brand Equity on Business Performance: RBV Perspectives) - Deccasari, Dwi Danesty; Andiani, Lidia; Sudiarto, Edi (Akutansi Bisnis & Manajemen ( ABM ), 2024)
This study aims to examine the influence of CSR on corporate reputation and brand equity, as well as its follow-up impact on business performance. Data was collected through the distribution of questionnaires to 160 owners. The results of the analysis show that CSR has a significant positive influence on the company's reputation and brand equity. A good reputation, in turn, will contribute to an increase in brand equity. The company's reputation and brand equity have proven to have a positive influence on business performance. This shows the importance of CSR as a business strategy that not only improves the company's image, but also has a positive impact on company performance. Besides, the implications of this study reveal the need for companies to develop the right metrics to measure the impact of CSR on the company, so that it can evaluate the effectiveness of the CSR programs that have been implemented.